3D absorptive frequency-selective reflection and transmission structures with dual absorption bands - Yu, Yufeng (2019)
This paper presents a 3D absorptive frequency-selective reflection structure (AFSR) and absorptive frequency-selective transmission structure (AFST) with one reflection/transmission band and two absorption bands. The 3D AFSR utilizes the intrinsic reflection band and higher order absorption band of a wideband 3D absorber. By simply loading a printed gap capacitor in the structure, the reflection band can be easily tuned by varying the capacitance of the capacitor. A design example is presented, with a reflection band of 24.7% fractional bandwidth (FBW), a lower absorption band of 72.5% FBW, and a higher absorption band of 48.6% FBW. A 3D AFST composed of the 3D AFSR and a parallel-plate waveguide is then proposed. Its general operating principle is demonstrated, such that the 3D AFST can be seen as a combination of a 3D AFSR and a 3D band-pass FSS, which can independently contribute to the absorption and transmission, respectively. A set of guidelines is proposed to facilitate the design. A prototype of the proposed AFST is fabricated and measured. The measured results show that the transmission band is with a minimum insertion loss of 0.4 dB and an FBW of 30%. Moreover, the lower and higher absorption bands are with 63.9 % and 47.6 % FBW, respectively. The proposed AFST has a simpler structure, wider lower absorption bandwidth, and thinner thickness compared with previous structures.